Geographic directions of migration processes influencing the formation of the demographic situation in East Kazakhstan during the years of independence (Journal of Geography and Environmental Management, 2021)
The article shows the trends and changes in migration processes in the East Kazakhstan region over the years of independence of Kazakhstan, as well as the intensity, volume and geography of migration flows, as well as statistics. The socio-economic prerequisites for the migration flows of the population of the region, their impact on the population, the quality of labor resources and the current conditions in the field of migration, as well as issues in the field of migration policy aimed at stabilizing the demographic situation in the region are presented.Analysis of the modern geography of migration processes in the East Kazakhstan region shows that it corresponds to the historical reality of 30 years of independence of the Republic of Kazakhstan, therefore, emigration had a negative impact on the history of the Republic of Kazakhstan at that time. about the demographic situation. The dynamics of changes in the balance of migration from 1992 to the present was characterized by negative indicators, and since 2016 the negative balance has grown again, which is 4.3 times higher than in 2015.Socio-economic consequences of migration flows (their scale, intensity, direction, etc.), Gender and age of migrants, social and ethnic composition and migration in the region. The results of the study showed the migratory movements of repatriates.A map of ethnic settlement in the East Kazakhstan region for 1999-2019 has been developed. Analyzed the political, economic and social factors affecting the demographic situation.
Keywords: migration flows, East Kazakhstan, migration, blood, migration balance, labor resources.